2012
DOI: 10.1007/978-3-642-33275-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal “Anti-Bayesian” Parametric Pattern Classification Using Order Statistics Criteria

Abstract: Abstract. The gold standard for a classifier is the condition of optimality attained by the Bayesian classifier. Within a Bayesian paradigm, if we are allowed to compare the testing sample with only a single point in the feature space from each class, the optimal Bayesian strategy would be to achieve this based on the (Mahalanobis) distance from the corresponding means. The reader should observe that, in this context, the mean, in one sense, is the most central point in the respective distribution. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 16 publications
5
50
0
Order By: Relevance
“…In line with the newly proposed OS-based anti-Bayesian classifiers [5,6,7], we created the "border" set by selecting those patterns which are close to the true border of the alternate class. The classification is achieved with regard to these border patterns alone, and the size of this set is very small, in some cases, as small as five from each class.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the newly proposed OS-based anti-Bayesian classifiers [5,6,7], we created the "border" set by selecting those patterns which are close to the true border of the alternate class. The classification is achieved with regard to these border patterns alone, and the size of this set is very small, in some cases, as small as five from each class.…”
Section: Discussionmentioning
confidence: 99%
“…The intriguing feature of these few points is that they lie close to the boundary and not to the mean, implying an "anti-Bayesian" philosophy [5,6,7].…”
Section: A Novel Two-class "Anti-bayesian" Bi Schemementioning
confidence: 98%
“…Earlier, in [1] and [2], we showed that we could obtain optimal results by an "anti-Bayesian" paradigm by using the OS. Interestingly enough, the novel methodology that we propose, referred to as Classification by Moments of Order Statistics (CMOS), is computationally not any more complex than working with the Bayesian paradigm itself.…”
Section: Introductionmentioning
confidence: 98%
“…The interesting point about these indicators is that some of them are quite unrelated to the traditional moments themselves, and in spite of this, have not been used in achieving PR. The amazing fact, demonstrated in [3] is that OS can be used in PR, and that such classifiers operate in a completely "anti-Bayesian" manner, i.e., by only considering certain outliers of the distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation